Endogenous stimulus-powered antibiotic release from nanoreactors for a combination therapy of bacterial infections - Wu, Yang; Song, Zhiyong; Wang, Huajuan; Han, Heyou (Nature communications, 2019)
The use of an endogenous stimulus instead of external trigger has an advantage for targeted and controlled release in drug delivery. Here, we report on cascade nanoreactors for bacterial toxin-triggered antibiotic release by wrapping calcium peroxide (CaO 2 ) and antibiotic in a eutectic mixture of two fatty acids and a liposome coating. When encountering pathogenic bacteria in vivo these nanoreactors capture the toxins, without compromising their structural integrity, and the toxins form pores. Water enters the nanoreactors through the pores to react with CaO 2 and produce hydrogen peroxide which decomposes to oxygen and drives antibiotic release. The bound toxins reduce the toxicity and also stimulate the body’s immune response. This works to improve the therapeutic effect in bacterially infected mice. This strategy provides a Domino Effect approach for treating infections caused by bacteria that secrete pore-forming toxins. Endogenous triggered delivery of antibiotics over an external triggered delivery has distinct advantages. Here, the authors report on a nanoreactor triggered by bacterial toxin to trigger a drug release mechanism and capture the toxin for reduced toxicity of toxins and improved immune response.